Controlling Neglected Tropical Diseases (NTDs) in Haiti: Implementation Strategies and Evidence of Their Success. - Jean Frantz Lemoine; Anne Marie Desormeaux; Franck Monestime; Carl Renad Fayette; Luccene Desir; Abdel Nasser Direny; Sarah Carciunoiu; Lior Miller; Alaine Knipes; Patrick Lammie; Penelope Smith; Melissa Stockton; et al. (Public Library of Science (PLoS), 2016)
Lymphatic filariasis (LF) and soil-transmitted helminths (STH) have been targeted since 2000 in Haiti, with a strong mass drug administration (MDA) program led by the Ministry of Public Health and Population and its collaborating international partners. By 2012, Haiti's neglected tropical disease (NTD) program had reached full national scale, and with such consistently good epidemiological coverage that it is now able to stop treatment for LF throughout almost all of the country. Essential to this success have been in the detail of how MDAs were implemented. These key programmatic elements included ensuring strong community awareness through an evidence-based, multi-channel communication and education campaign facilitated by voluntary drug distributors; strengthening community trust of the drug distributors by ensuring that respected community members were recruited and received appropriate training, supervision, identification, and motivation; enforcing a "directly observed treatment" strategy; providing easy access to treatment though numerous distribution posts and a strong drug supply chain; and ensuring quality data collection that was used to guide and inform MDA strategies. The evidence that these strategies were effective lies in both the high treatment coverage obtained- 100% geographical coverage reached in 2012, with almost all districts consistently achieving well above the epidemiological coverage targets of 65% for LF and 75% for STH-and the significant reduction in burden of infection- 45 communes having reached the target threshold for stopping treatment for LF. By taking advantage of sustained international financial and technical support, especially during the past eight years, Haiti's very successful MDA campaign resulted in steady progress toward LF elimination and development of a strong foundation for ongoing STH control. These efforts, as described, have not only helped establish the global portfolio of "best practices" for NTD control but also are poised to help solve two of the most important future NTD challenges-how to maintain control of STH infections after the community-based LF "treatment platform" ceases and how to ensure appropriate morbidity management for patients currently suffering from lymphatic filarial disease.